Pengaruh Lingkungan Individu Mahasiswa dan Kinerja Bauran Pemasaran Perguruan Tinggi terhadap Proses Keputusan Mahasiswa dan Nilai Jasa Pendidikan Tinggi Komputer - Harjanto Prabowo (Bina Nusantara University, 2012)
Colleges that offer computer education are increasing, partly because of the widespread use of information technology in all areas of life so that it takes labors/computer graduates qualified and applicably ready. This situation also occurs in colleges at Jakarta. This paper presents the results, which aims to reveal the compatibility level of educational services mixed-marketing performance with the interests and expectations of college students. Research conducted is descriptive and verification, while the method of research is an explanatory survey method to 770 students of computer private universities in Jakarta and 54 leaders in computer private universities in Jakarta. The results show that the environment of one individual affects more to college students in processing decision to choose the college compared to educational services mixed-marketing performance. Whereas, the value of education services is not affected by the environmental of students but by educational services mixed-marketing performance and student decision process. There is a mismatch/gap between the educational service mixed-marketing performance to the level of expectations and interests level of students perceived.